1988
DOI: 10.1111/j.1365-246x.1988.tb06709.x
|View full text |Cite
|
Sign up to set email alerts
|

On the relation between days of small amplitude of Sq(H) and abnormal quiet days

Abstract: S U M M A R YIn order to explain the results of a previous study of the variations in declination at Hermanus on abnormal quiet days at Hartland, it has been proposed that a single current vortex system spanning both hemispheres links the variations at the two stations (Butcher 1987). Earlier work (Butcher & Brown 1981) suggested that an abnormal quiet day results from the combination of the Occurrence of a day of low range in S q ( H ) and a small magnetospheric substorm or mini-bay which therefore forms the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…What switches the SCV on and off is not known. AQDs are probably just a n indication of the occurrence of days of small amplitude in S q ( H ) (Schlapp, Mann & Butcher 1988) and it is therefore possible that the SCV is present with greater or lesser strength on most days. If this is so and it is of ionospheric origin, its generation could be of local origin or possibly associated with the variability in the winds that generate the Sq currents, particularly interhemispheric variabilities in the amplitudes of the asymmetric tidal modes.…”
Section: Discussionmentioning
confidence: 99%
“…What switches the SCV on and off is not known. AQDs are probably just a n indication of the occurrence of days of small amplitude in S q ( H ) (Schlapp, Mann & Butcher 1988) and it is therefore possible that the SCV is present with greater or lesser strength on most days. If this is so and it is of ionospheric origin, its generation could be of local origin or possibly associated with the variability in the winds that generate the Sq currents, particularly interhemispheric variabilities in the amplitudes of the asymmetric tidal modes.…”
Section: Discussionmentioning
confidence: 99%
“…The pair of field-aligned currents near the dawn and dusk meridians was surmised by Schlapp et al (1988) after their comparison of the Sq variation observed at two middle latitude stations in the northern and southern hemispheres. Maeda and Murata (1965) first pointed out the possibility of the existence of a pair of field-aligned currents in the morning (summer-to-winter direction) and in the afternoon (winter-to-summer) associated with the Sq currents in the solstitial season.…”
Section: Electric Currentmentioning
confidence: 99%